French enlighteners and Uzbek modernists about human rights - A.S. Ganiev (Periodica Journal, 2023)
This article highlights the influence of the legacy of the French enlighteners of the XVIII th century on the XIX th Uzbek modernists in the formation of the freedom of human rights and organizing the activities of new ethod schools.
Keywords: Eighteenth-century French Enlightenment; Enlightenment legacy; Modernism; Human rights and freedom